Action Research to Improve Online Teaching and Learning Activities at STIE Indonesia Banjarmasin - Said, Meldasari; Fahrianta, Riswan Yudhi (Jurnal Manajemen, 2024)
This study aims to analyze the readiness STIE Indonesia Banjarmasin students in facing online learning, and what actions are good to take so that learning outcomes can be achieved. This study used action research methods. The method of data collection through observation of three classes with a total of 145 students, complemented by interviews with eight students from representatives of each class as informants. Observations were made in three cycles, namely online synchronous class cycle, the online asynchronous cycle using video, and the online asynchronous cycle using video plus quizzes. Each cycle goes through four stages, namely design, implementation, evaluation, and rethink. The results show that postgraduate students prefer online classes because it saves travel costs and is more flexible in terms of time. They prefer synchronous classes because there is direct interaction. While undergraduate students prefer offline classes so they can focus, avoid a non-conducive learning environment. In addition, for the learning method with video, it is more effective if it is added with a quiz at the end of the material to increase students’ access to watching online learning videos.